(untitled) (Bangladesh Journal of Microbiology, 2016)
Present study dealt with identification of some heavy metal tolerant bacteria from contaminated industrial soils of Dhaka Export Processing Zone (DEPZ) at Savar, tannery area at Hazaribagh and uncontaminated agricultural soils of Dhamrai and Kushtia in Bangladesh and determination of their tolerance to chromium (Cr6+) and cadmium (Cd2+). A total of 15 isolates from four soil samples were provisionally identified as different species of Bacillus, Micrococcus and Pseudomonas based on their morphological, physiological, and biochemical characteristics. Among them eight colonies were separated based on high level of heavy metal tolerance and identified at molecular level by PCR technique and 16S rRNA gene sequencing as Micrococcus luteus strain P43 (E4), Bacillus pocheonensis strain TR2-6 (T6), Bacillus megaterium strain H2 (T8), Bacillus amyloliquefaciens strain SCSAAB0007 (D10), Bacillus cereus isolate PGBw4 (D11), Bacillus cereus strain ES-4a1 (K12), Bacillus subtilis strain 1320, (K13), and Bacillus subtilis strain DP14 (K14). The Maximum Tolerable Concentration (MTC) of bacterial strains to Cr6+ and Cd2+ ranged between 250-1250 ?g/ml and 30-150 ?g/ml, respectively in nutrient broth medium. From the metal tolerance investigation Bacillus was found as the most heavy metal tolerant to both Cr6+ and Cd2+ among the three genera. The identified heavy metal tolerant bacteria could be useful for the bioremediation of heavy metal contaminated environment. Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 56-61